A Case of Tuberculosis-related Cerebral Venous Sinus Thrombosis and Pulmonary Thromboembolism Successfully Treated with Edoxaban. (2022) - Nishino, Koichi; Akimoto, Takashi; Mitsuoka, Hideyuki; Terajima, Yutaka; Arai, Yuta; Masui, Yoshihiro; Mimori, Tomoyasu; Koike, Kengo; Takahashi, Kazuhisa; Sekiya, Mitsuaki
Abstract: A 22-year-old woman was admitted to the hospital with complaints of headache and vomiting. Radiological examinations revealed cerebral sinus venous thromboses, pulmonary thromboembolism, and cavities in the left upper lung. Pulmonary tuberculosis was diagnosed based on sputum and gastric aspirate culture. Heparin followed by warfarin was administered. Anti-tuberculosis agents including rifampicin were also initiated. Since the effect of warfarin did not reach the therapeutic level because of interaction with rifampicin, edoxaban was administered and thromboses were ameliorated. This report illustrates rare thrombotic complications in a TB-induced hypercoagulable state and the potential benefits and safety of edoxaban in combination with rifampicin.